Analisa Debit Run-Off Daerah Aliran Sungai Gembong Menggunakan Metode Fj Mock - Risa Arofi, Faisal; Maulidiyah, Afrikhatul (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
The Gembong River Basin (DAS) in Pasuruan Regency is an agricultural area heavily influenced by surface water availability. High rainfall fluctuations and limited natural reservoirs pose a risk of water deficit during the dry season. This study aims to analyze runoff discharge, reliable discharge, and water balance using the FJ Mock method based on monthly rainfall data, potential evapotranspiration, and watershed physical characteristics. The data used covers the period 2010–2024, which is processed to produce effective rainfall, monthly discharge, reliable discharge (Q80), and annual water balance. The calculation results show a maximum discharge of 5.83 m³/s in December and a minimum discharge of 0.76 m³/s in October. The average reliable discharge value of Q80 is only around 0.01–0.02 m³/s, indicating limited water supply during the dry season. The water balance shows a period of water surplus occurring in January–June, while a deficit occurs in July–December. These findings emphasize the need for integrated water resource management strategies, such as the construction of reservoirs and adjustments to cropping patterns based on reliable discharge to ensure the sustainability of irrigation.